2021
DOI: 10.1093/brain/awab011
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal tau species transfer to astrocytes and induce their loss according to tau aggregation state

Abstract: Deposits of different abnormal forms of tau in neurons and astrocytes represent key anatomo-pathological features of tauopathies. Although tau protein is highly enriched in neurons and poorly expressed by astrocytes, the origin of astrocytic tau is still elusive. Here, we used innovative gene transfer tools to model tauopathies in adult mouse brains and to investigate the origin of astrocytic tau. We showed in our adeno-associated virus (AAV)-based models and in Thy-Tau22 transgenic mice that astrocytic tau pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 61 publications
3
23
0
Order By: Relevance
“…Astrocytes can also uptake tau pathology, which can be enhanced by lysosomal function. Mate De Gerando et al ( 2021 ) confirmed that tau can be transferred between neurons and astrocytes in vivo in a mouse model by expressing a pro-aggregating tau peptide in neurons and human wild-type tau in astrocytes in the hippocampus. Using an antibody that only detects the aggregates formed by co-expression of both forms of tau, positive tau-aggregate staining was observed in both cell types, indicating transfer of tau species between neurons and astrocytes.…”
Section: Glial Role In Propagation Of Neurodegenerative Pathologymentioning
confidence: 95%
See 1 more Smart Citation
“…Astrocytes can also uptake tau pathology, which can be enhanced by lysosomal function. Mate De Gerando et al ( 2021 ) confirmed that tau can be transferred between neurons and astrocytes in vivo in a mouse model by expressing a pro-aggregating tau peptide in neurons and human wild-type tau in astrocytes in the hippocampus. Using an antibody that only detects the aggregates formed by co-expression of both forms of tau, positive tau-aggregate staining was observed in both cell types, indicating transfer of tau species between neurons and astrocytes.…”
Section: Glial Role In Propagation Of Neurodegenerative Pathologymentioning
confidence: 95%
“…More recently, astrocytes have been implicated in the propagation of pathogenic protein aggregates. While astrocytes do not express α-syn they have been observed to uptake cytoplasmic pre-aggregate species and oligomeric fibrils of α-syn more readily than neurons (Lee et al, 2010 ; Gustafsson et al, 2017 ; Loria et al, 2017 ; di Domenico et al, 2019 ; Tsunemi et al, 2020 ) They have also been shown to uptake Aβ proto-fibrils and aggregates (Mulder et al, 2014 ; Sollvander et al, 2016 ; Nilson et al, 2017 ) and tau monomeric species, pre–formed tau fibrils, and phosphorylated tau aggregates (Martini-Stoica et al, 2018 ; Perea et al, 2019 ; Mate De Gerando et al, 2021 ). Furthermore, astrocytes uptake Aβ more readily when packaged within EVs (Dinkins et al, 2016 ), as well as α-syn associated with EVs (Tsunemi et al, 2020 ).…”
Section: Glial Role In Propagation Of Neurodegenerative Pathologymentioning
confidence: 99%
“…This minimizes the induction of tau pathology in the brainstem and spinal cord like many transgenic animals, which is associated with undesirable functional consequences (e.g., paralysis). Thirdly, they can include a cell type-specific promoter to select the cell type bearing the tau pathology (e.g., astrocytes) [ 99 , 100 ]. Likewise, they can include a fluorophore (e.g., green fluorescent protein (GFP), which labels transduced cells, thereby differentiating them from recipient cells.…”
Section: Animal Models Of Tau Propagationmentioning
confidence: 99%
“… Repair after CNS damage including glial scar formation [ 1 ]. Production of pro-and anti-inflammatory cytokines in response to infection and injury [ 25 ]. …”
Section: Overview Of Astrocyte Biology and Functionmentioning
confidence: 99%
“…Importantly, homogenates from human ARTAG cases containing TSAs only and inoculated into wild-type mice have been able to produce tau propagation in astrocytes, oligodendrocytes, neurons and white matter fibres, showing that astrocytes are highly involved in tau propagation [ 66 ]. Further work by the same group showed that human ARTAG homogenates propagated tau in wild-type mice, but mostly in neurons and oligodendrocytes [ 96 ], and recent studies have demonstrated that astrocytic pathology does not propagate in the absence of neuronal tau [ 25 , 97 ], suggesting there are other propagation factors at play. Perhaps clues may be derived from a cell culture propagation model, where human PiD brain extracts were used to infect HEK293T cells expressing 3R tau and extracts from AGD, CBD, and PSP human samples were transmitted to HEK293 cells expressing 4R tau.…”
Section: Astrocytic Tau Propagationmentioning
confidence: 99%